2017
DOI: 10.1039/c7ta01008g
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional CoNi nanoparticles@S,N-doped carbon composites derived from S,N-containing Co/Ni MOFs for high performance supercapacitors

Abstract: CoNi alloy nanoparticles incorporated into S,N-doped carbon structure was obtained by pyrolysis treatment of 2D S,N-containing Co/Ni MOFs nanosheets, as electrode material exhibiting high supercapacitor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…Therefore, substituting Pf or Sd id not change the crystal structure or lattice parameters because Sa nd Ph ad similara tomics izes. [33][34][35][36][37][38] In short, P-CoS comprised Co 2 + ,Co 3 + ,S 2À ,and P dÀ . SEM providesf urtheri nsights into the morphologies and geometrical structures of Co 3 O 4 ,C oS and P-CoS.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, substituting Pf or Sd id not change the crystal structure or lattice parameters because Sa nd Ph ad similara tomics izes. [33][34][35][36][37][38] In short, P-CoS comprised Co 2 + ,Co 3 + ,S 2À ,and P dÀ . SEM providesf urtheri nsights into the morphologies and geometrical structures of Co 3 O 4 ,C oS and P-CoS.…”
Section: Resultsmentioning
confidence: 99%
“…The capacitance of the Na−Mn−O 550 composite is larger than many formerly reported Na−Mn−O composites (Table S1), which is further confirmed that the facile molten salt method is one of the effective approaches for the preparation of the supercapacitor electrode materials. Moreover, the specific capacitance of the both composites decreases gradually as the current density grows, which would be due to the low utilization and transport limitation of ions into the interior electroactive sites of the electrode materials . This phenomenon is an indication of a diffusion‐controlled process …”
Section: Resultsmentioning
confidence: 99%
“…At a scan rate of 1 mV s −1 , their specific capacitances were 295 F g −1 for N-PCMPs-A and 180 F g −1 for N-PCMPs. When the scan rate increased to 50 mV s −1 , the N-PCMPs-A exhibited better capacitance retention (194…”
Section: Other Zif-derived Carbonsmentioning
confidence: 99%
“…Co 9 S 8 -containing composite with the inclusion of 2D CoNi alloys NPs into S/N-co-doped carbon nanosheets (CoNi@SNC) was fabricated from the 2D Co/Ni-MOF nanosheets [194]. The S,N-containing Co/Ni-MOFs were synthesized under mild basic condition at room temperature using mixed metal sources (CoCl 2 •6H 2 O and NiCl 2 •6H 2 O) and two different bridging linkers (tdc = thiophene-2,5-dicarboxylate, 4.4 -bpy = 4,4 -bipyridine).…”
Section: Composites Containing Carbon/metal Sulfide Composites Contaimentioning
confidence: 99%